Gandhi [videorecording (DVD)] - Briley, John; Kingsley, Ben, 1943-; Bergen, Candice, 1946-; Fox, Edward, 1937-; Gielgud, John, 1904-2000; Howard, Trevor, 1916-1988; Mills, John, 1908-2005; Sheen, Martin; Charleson, Ian; Fugard, Athol; Halmer, Gunther Maria, 1943-; Jaffrey, Saeed, 1929-2015; et al. (Columbia Pictures, 1982)
Chronicles the life of Gandhi beginning with his political activities in South Africa during the late 1890's and ending with his assassination at the hands of a Hindu extremist in 1948. Shows the development of his philosophy of non-violence as he leads the people of India to independence from the British.